Iron Targeted Transcriptome Study Draws Attention to Novel Redox Protein Candidates Involved in Ferrous Iron Oxidation in “Ferrovum” Sp. ja12 - Levican-Jaque, G (Elsevier Masson SAS, 2018)
The response of the acidophilic iron oxidizer “Ferrovum” sp. JA12 to elevated concentrations of ferrous iron was targeted at transcriptome level in order to assess models on oxidative stress management and ferrous iron oxidation. Overall transcriptome profiles indicate a high cellular activity of “Ferrovum” sp. JA12 up to 50 mM of ferrous iron with genes predicted to be involved in iron oxidation, carbon fixation and ribosome formation showing the highest transcript levels. The data support the iron oxidation pathway inferred from genome analysis and draws attention to further redox proteins potentially associated with iron oxidation. The restriction of homologous proteins to iron oxidizing beta- and zetaproteobacteria underlines the previous notion of a common origin of iron oxidation in these phyla. Detoxification of reactive oxygen species and primary products of oxidative damage of membrane lipids appears to be of permanent relevance under conditions mimicking those of the original habitat of “Ferrovum” sp. JA12. Also the maintenance of a reverse membrane potential appears to be its most important strategy to withstand the acidic external pH. © 2018 Institut Pasteur